Capacitor-Current-Feedback With Improved Delay Compensation for LCL-Type Grid-Connected Inverter to Achieve High Robustness in Weak Grid - Tieying Zhao; Junran Li; Ning Gao (IEEE Access, 2022)
To attenuate the resonance of the LCL filter, capacitor-current-feedback (CCF) active damping has been extensively adopted in LCL-Type grid-connected inverters. Owing to the appearance of a negative damping region caused by the digital control delay, however, the damping performance has significantly deteriorated, thus the system is susceptible to being unstable under weak grid operation. To address this issue, this paper proposes an improved delay compensation method, which can effectively extend the boundary frequency of the positive equivalent resistance region from $f_{s}/6$ to $f_{s}/4$ . Furthermore, the resonance frequency forbidden region of the LCL filter can be eliminated. In doing so, strong robustness against the grid impedance variation and high noise immunity can be achieved. To guarantee the system stability and obtain good control performance after compensation, a detailed parameters design procedure for the current regulator and the CCF coefficient is further presented. At last, experimental results are provided to confirm the theoretical analysis and verify the effectiveness of the proposed delay compensation method.